Dampak penerapan LKS virtual laboratorium terintegrasi pendekatan saintifik pada materi fluida statis dan dinamis di kelas XI - fitri rahmi; masril masril; Yenni Darvina; Hidayati Hidayati (Universitas Negeri Padang, 2019)
Physics learning requires students to be able to carry out practical activities. Practical activities can be carried out if the practical tools and materials available. But in reality implementation of practicum is not optimal because lack of tools and materials. One solution that can be done is to do a virtual lab. In implementing virtual labs, a guide is needed in the form of a virtual lab worksheet. The application of virtual lab worksheets is integrated into critical thingking, creative, collaborative and communicative (4C) skills. The purpose of this research is to determine the effect of virtual lab worksheets integrated 4C skills on student competence in static and dynamic fluid in class XI SHS 4 Padang. This research used Quasi Experiment Research with Posstest Only Control Group Design as research design. The population of this research is all of the second grade student of SHS 4 Padang in 2018/2019 year study. The result of this research showed there is a the difference of Mean between sample classes significantly. The correlation coefficient between the application of virtual lab worksheets to the achievement of attitude competence is 0,84,knowledge competencies is 0,86 and skills competence is 0,94. Coefficient determination of attitude competence is 70,56%, knowledge competence is 74%, and skills competence is 89%. This means that the application of virtual lab worksheets influences the achievement of competency in class XI high school students.